Hope, social relations, and mental health outcomes of parents of children with moderate severe autism - Azhari Md Ghazali (2017)
Parents of children with autism spectrum disorder (ASD) face many challenges upbringing their children as these children usually have significant problems in communication, social interaction and unusual repetitive behaviours. Therefore, this study investigates how hopeful thinking in parents can produce positive outcomes by examining the relationship between hope, social support (friend and family support) and symptoms of depression. In the study, 32 parents (16 mothers, 16 fathers) of children aged 7 to 18 from various special education school in Singapore completed a survey questionnaire which consists of 4 sections: parental hope, parental loneliness, parental social support and parental mental health. A series of mediation model was tested in the study. The result in the models with multiple mediation shows that with increased levels of hope, it decreased the levels of loneliness and subsequently decreased symptoms of depression in both parents. On the other hand, there are no significant results in the model with serial mediation in the study even though it shows that fathers have lower levels of loneliness compared to mothers. Lower level of loneliness in fathers compared to mothers would then suggest that mothers are the main caregivers of their children and possibly receive less or no social support from friends and family members. The study suggests that hope is associated with decreased symptoms of depression and loneliness is the key variable with the capability of demonstrating this relationship in both parents. Keywords: Autism spectrum disorder, Parents, Hope